Klippel-Feil syndrome: a case report - Patel, Meena; Gupta, Richa; Bajaj, Naresh; Tagore, Vinod (International Journal of Research in Medical Sciences, 2017)
Klippel-Feil Syndrome (KFS) is defined as congenital fusion of two or more cervical vertebrae. The most common signs are short neck, low hairline at the back of head and restricted mobility of neck. We report a case of a neonate who presented with complaint of respiratory difficulty and later diagnosed as case of Klippel-Feil syndrome.